Le traitement du bagne colonial de Guyane par le magazine Détective - Jean-Lucien Sanchez (Criminocorpus)
The penal colony of French Guyana was one of favorite investigative themes of the newspaper Détective. The reporters traveled to French Guyana to visit the penitentiaries and could thus inform the readers of the fate of convicts whose Détective had frequently covered the conviction in court. Wishing to orientate these reports in a favorable direction, the Colonial Ministry was doing everything possible to facilitate the work of the journalists. But the treatment of the penal colony by Détective displeased to the authorities which quickly forbade the journalists to reach the penitentiaries. However, they continued to get on spot and report back to the public. At the same time, Détective’s tone became openly abolitionist, accompanying and mediating various legislative initiatives initiated in Parliament from the 1930s onwards.